2016
DOI: 10.1007/s13353-016-0384-z
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of mitochondrial DNA in three Arabian horse strains

Abstract: Arabian horse registries classify Arabian horses based on their dam lineages into five main strains. To test the maternal origin of Syrian Arabian horses, 192 horses representing the three major strains Saglawi, Kahlawi, and Hamdani were sequenced for 353 bp of their mitochondrial displacement loop (D-loop) region. Sequencing revealed 28 haplotypes comprising 38 sequence variations. The haplotype diversity values were 0.95, 0.91, and 0.90 in Kahlawi, Hamdani, and Saglawi strains, respectively. The pair-wise po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…1 ) showing high genetic diversity among them which was similar to the study by Khanshour et al, (2013) . One of the studies based on mitochondrial D-Loop revealed comparable result to this current study of Kehilan diversity than Seglawi and Hamdani ( Almarzook et al, 2017 ). The variations in the mitochondrial genome of protein-coding genes revealed that Hamdani and Hadban are more closely related than Seglawi and Kehilan horses.…”
Section: Discussionsupporting
confidence: 83%
“…1 ) showing high genetic diversity among them which was similar to the study by Khanshour et al, (2013) . One of the studies based on mitochondrial D-Loop revealed comparable result to this current study of Kehilan diversity than Seglawi and Hamdani ( Almarzook et al, 2017 ). The variations in the mitochondrial genome of protein-coding genes revealed that Hamdani and Hadban are more closely related than Seglawi and Kehilan horses.…”
Section: Discussionsupporting
confidence: 83%
“…However, it is possible to illustrate the potential development of haplotypes within the haplogroups using a median-joining network (Figure 4). Median-joining networks are applied to reconstruct intraspecific phylogenies (Bandelt et al, 1999) and have been widely used in mtDNA studies for intra-and interbreed comparisons in horses (Cieslak et al, 2010;Campana et al, 2012;Almarzook et al, 2017). A common ancestral haplotype can be identified within each haplogroup as origin from which all the other haplotypes probably have developed.…”
Section: Potential Evolution Of Lineagesmentioning
confidence: 99%
“…Recently, mitochondrial DNA polymorphisms have been widely used to estimate the gene flow and phylogenetic relationships of maternal lineages in domestic animals (e.g., Nguluma et al, 2017;Jia et al, 2017;Deng et al, 2017;Almarzook et al, 2017) and wild animals (e.g., Elsner et al, 2017;Khaire et al, 2017). The domestic yak (Bos grunniens) is a large and commercially important animal living in the Qinghai-Tibetan Plateau of China with a high-altitude climate (Guangxin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%